2018
DOI: 10.1080/07853890.2018.1432887
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension and exercise training: a synopsis on the more recent evidences

Abstract: The benefits of exercise training in virtually all humans, including those with a clinically stable chronic disease are numerous. The potential value lies in the fact that functional capacity is oftentimes significantly compromised. Exercise training not only play a role in reversing some of the pathophysiologic processes associated with chronic diseases but also improves clinical trajectory. Given the significant pathologic consequences associated with pulmonary hypertension and its implications for deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Physical activity is one of the most important modifiable factors in our lifestyle and may significantly impact the prevention and treatment of cardiovascular diseases [ 21 ]. Exercise may modulate a variety of molecular mechanisms related to proliferation, apoptosis, oxidative stress, inflammation, thrombosis, proteolysis, and vasodilatation [ 19 , 22 , 23 ].…”
Section: Main Components Of the Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is one of the most important modifiable factors in our lifestyle and may significantly impact the prevention and treatment of cardiovascular diseases [ 21 ]. Exercise may modulate a variety of molecular mechanisms related to proliferation, apoptosis, oxidative stress, inflammation, thrombosis, proteolysis, and vasodilatation [ 19 , 22 , 23 ].…”
Section: Main Components Of the Exercise Trainingmentioning
confidence: 99%
“…There is also insufficient data on what forms, frequencies, and intensities of exercise are required to obtain the most beneficial results [ 23 , 24 , 26 , 27 , 28 ]. The available literature shows that in addition to daily activity, regular endurance (or aerobic) training, strength training, and respiratory muscle training ought to be done [ 3 , 21 , 29 , 30 , 31 ]. Aerobic, resistance, and inspiratory muscle training, supported by individually adapted general conditioning training (also known as general fitness), stretching, body awareness training, neuromuscular relaxation techniques, positional relaxation, fascial therapy, etc., provide significant functional and physiological improvement [ 29 , 30 ].…”
Section: Main Components Of the Exercise Trainingmentioning
confidence: 99%
“…6 It has now been established that exercise in patients with pulmonary hypertension is safe and leads to improvements in functional ability and quality of life. 7,8 While further work is required to fully understand the physiological effects of exercise training in patients with pulmonary hypertension, 9 change in skeletal muscle function and cardiac function as well as reversal of pre-existing deconditioning are potential mechanisms. 10,11 In a systematic review of studies of exercise therapy in pulmonary hypertension, Morris et al 12 demonstrated improvements in six-minute walk distance of 60 m as well as significant improvements in quality of life and only a single adverse event (light-headedness during exercise) across 206 study participants.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest and a growing evidence base for exercise training in patients with pulmonary hypertension since the first randomised controlled trial in 2006 6 . It has now been established that exercise in patients with pulmonary hypertension is safe and leads to improvements in functional ability and quality of life 7 , 8 . While further work is required to fully understand the physiological effects of exercise training in patients with pulmonary hypertension, 9 change in skeletal muscle function and cardiac function as well as reversal of pre‐existing deconditioning are potential mechanisms 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The current World Symposium on Pulmonary Hypertension (WSPH) classification of PH is based on a combination of patient characteristics, clinical features and cardiopulmonary hemodynamics and these WHO groups are used to inform drug treatment options ( Simonneau et al, 2013 ). Recently, PH interventions based on supervised exercise training and nightly oxygen have been developed that have significant therapeutic effect to a degree that is expected from adding another drug for multi-drug treatment of PH ( Mereles et al, 2006 ; Grunig et al, 2011 , 2012a , b ; Nagel et al, 2012 ; Becker-Grunig et al, 2013 ; Schumacher et al, 2014 ; Pandey et al, 2015 ; Ulrich et al, 2015 ; Ehlken et al, 2016 ; Gonzalez-Saiz et al, 2017 ; Keusch et al, 2017 ; Moreira-Goncalves et al, 2017 ; Richter et al, 2017 ; Leggio et al, 2018 ). Already after a 3-week period, supervised exercise training improved, for example, the 6MWD and hemodynamics, which are important signs for PH prognosis ( Grunig et al, 2012a , b ).…”
Section: Introductionmentioning
confidence: 99%